Genome-scale CRISPR-Cas9 knockout screening in nasopharyngeal carcinoma for radiosensitive and radioresistant genes - Ziyan Zhou; Gang Chen; Mingjun Shen; Jixi Li; Kang Liu; Ming Liu; Shuo Shi; Dong Yang; Wei Chen; Sixia Chen; Yuanxiu Yin; Yating Qin; et al. (Translational Oncology, 2023)
Background: Genome-scale CRISPR-Cas9 knockout screening may provide new insights into the mechanism underlying clinical radioresistance in nasopharyngeal carcinoma (NPC), which is remain largely unknown. Our objective was to screen the functional genes associated with radiosensitivity and radioresistance in NPC, laying a foundation for further research on its functional mechanismand. Methods: CRISPR-Cas9 library lentivirus screening in radiation-treated NPC cells was combined with second-generation sequence technology to identify functional genes, which were further validated in radioresistant NPC cells and patient tissues. Results: Eleven radiosensitive and radioresistant genes were screened. Among these genes, the expression of FBLN5, FAM3C, MUS81, and DNAJC17 were significantly lower and TOMM20, CDKN2AIP, SNX22, and SP1 were higher in the radioresistant NPC cells (C666-1R, 5-8FR) (p < 0.05). CALD1 was highly expressed in C666-1R. Furthermore, we found knockout of FBLN5, FAM3C, MUS81 and DNAJC17 promoted the proliferation of NPC cells, while CDKN2AIP and SP1 had the opposed results (p < 0.05). This result was verified in NPC patient tissues. Meanwhile, KEGG analysis showed that the Fanconi anemia pathway and the TGF-β signaling pathway possibly contributed to radiosensitivity or radioresistance in NPC. Conclusions: Nine genes involved in the radiosensitivity or radioresistance of NPC: four genes for radiosensitivity (FBLN5, FAM3C, MUS81, and DNAJC17), two genes for radioresistance (CDKN2AIP, SP1), two potential radioresistant genes (TOMM20, SNX22), and a potential radiosensitive gene (CALD1). Genome-scale CRISPR-Cas9 knockout screening for radiosensitive and radioresistant genes in NPC may provide new insights into the mechanisms underlying clinical radioresistance to improve the efficacy of radiotherapy for NPC.